PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN WAJIB PAJAK RESTORAN BADAN PENDAPATAN DAERAH KOTA MAKASSAR - Kiki Angreni; Fatmawati Fatmawati; Nuryanti Mustari (JPPM: Journal of Public Policy and Management, 2022)
This study aimed to find out the influence of the service quality variable on the restaurant taxpayer satisfaction variable at the Makassar City Regional Revenue Agency. This study used quantitative research methods. Data were analyzed using descriptive statistics with a simple linear regression formula. The data  was  explained in the form of tables, frequencies, images, and narration by using IBM SPSS Version 21. The results of this study at the Makassar City Regional Revenue Agency showed that the influence of service quality on taxpayer satisfaction was not significant. From the results of the analysis, it could be concluded that service quality had a strong influence on taxpayer satisfaction. This  seen from the results of the determination test, it was known that the R2 value was 0.065, which meant 6.5%. It indicated that service quality was influenced by employee performance and the rest was influenced by other variables. Values on service quality such as: efficiency, effectiveness, fairness, and responsiveness do not contribute to taxpayer satisfaction.